Magnetic field losses in Nd-Fe-B magnets under 10 MeV electron irradiation - Bovda, V.A.; Bovda, A.M.; Guk, I.S.; Dovbnya, A.N.; Lyashchenko, V.N.; Mytsykov, A.O.; Onischenko, L.V.; Kalinichenko, A.I.; Kandybei, S.S.; Repikhov, O.A. (Вопросы атомной науки и техники, 2017)
Reversible changes in magnetic properties of Nd-Fe-B magnets under electron beam with the energy of 10 MeV and bremsstrahlung irradiation were investigated. It was shown that direct electron beam irradiation resulted in the decrease of magnetic flux and substantial alteration in the magnetic pattern on the surface of the samples. Increasing the radiation dose in 10 times did not lead to a linear reduction of magnetic flux. Bremsstrahlung also did not produce any significant drop in magnetic performance. Re-magnetization after the irradiation allowed to restore the initial magnetic properties of Nd-Fe-B magnets.